Survey on analysis of energy optimization in MANET routing - Baby, Basil; R Suji Pramila, Dr (International Journal of Engineering and Technology, 2018)
Mobile Adhoc Network (MANET) is becoming a priority in everyday life due to its flexibility and scalability in networking. All mobile applications using networks are ready to share and receive data and so they are capable of supporting infrastructure less networks. This leads to become MANET a prominent networking solution worldwide. So the research eyes are now focused on how to improve the MA-NET performance. There are so many aspects to be analyzed to improve the performance of the MANET. Load balancing is such a critical issue to be addressed seriously to attain maximum throughput from the MANET. Effective Load balancing can be attained by disseminating data traffic among the mobile nodes so that the equilibrium of the MANET is not violated. This ensures the stability of the entire network which will result in maximum throughput and fault tolerance. This paper analyses and compare the effect of energy optimization used in various existing methods and how better load balancing is achieved.Â Â